1999
DOI: 10.2172/15170
|View full text |Cite
|
Sign up to set email alerts
|

Geologic Data Package for 2001 Immobilized Low-Activity Waste Performance Assessment

Abstract: This database is a compilation of existing geologic data from both the existing and new immobilized low-activity waste disposal sites for use in the 2001 Pefiorrnance Assessment. Data were compiled from both surface and subsurface geologic sources. Large-scale surface geologic maps, previously published, cover the entire 200-East Area and the disposal sites. Subsutiace information consists of drilling and geophysical logs from nearby boreholes and stored sediment samples. Numerous published geological reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…However, the materials penetrated below this depth generally consisted of stratified sand deposits, with variable silt content, and rare pebbles. This is consistent with the third layer (Layer 3) of a sandy sequence described by Reidel and Horton (1999) Figure 3. Grain size nomenclature (after Wentworth, 1922) and sediment classification scheme (modified after Folk, 1968) used at the Hanford Site…”
Section: Geologic Field Descriptionssupporting
confidence: 87%
“…However, the materials penetrated below this depth generally consisted of stratified sand deposits, with variable silt content, and rare pebbles. This is consistent with the third layer (Layer 3) of a sandy sequence described by Reidel and Horton (1999) Figure 3. Grain size nomenclature (after Wentworth, 1922) and sediment classification scheme (modified after Folk, 1968) used at the Hanford Site…”
Section: Geologic Field Descriptionssupporting
confidence: 87%
“…Flood sediments were deposited when ice dams in western Montana and northern Idaho were breached, and massive volumes of water spilled across eastern and central Washington. This process repeated itself numerous times prior to about 13,000 years, bringing to the Plateau a thick sequence of sediments known as the Hanford formation (Reidel and Horton 1999). The surface soil at the site is a coarse sand, locally known as a Quincy sand, which is associated with the Quincy soil series (mixed, mesic, Xeric Torripsamments).…”
Section: 2mentioning
confidence: 99%
“…The materials penetrated below this depth generally consisted of stratified sand deposits, with variable silt content and rare pebbles. Last and Caldwell (2001) reported that these materials were consistent with the third layer (Layer 3) of a sandy sequence described by Reidel and Horton (1999) within the uppermost Hanford formation beneath the southeast portion of 200 East Area. The latest ILAW borehole 299-E24-21 confirmed the presence of a thick bedded sand sequence from near the surface to ~91.5 m (300 ft) depth.…”
Section: Geologic Descriptionsmentioning
confidence: 62%